Permeable membrane dewatering of faecal sludge from pit latrines at a transfer station in Nairobi, Kenya. Issue 14 (20th June 2022) - Rhodes-Dicker, Leandra; Ward, Barbara J.; Mwalugongo, Wali; Stradley, Lindsay
ABSTRACT: Faecal sludge dewatering is often a necessary step in many treatment and reuse processes, and it can decrease costs of transporting large volumes of high water content sludge. Common dewatering methods such as settling-thickening tanks and drying beds are not feasible in space-constrained areas such as urban informal settlements, therefore innovative dewatering methods are needed. This study evaluated permeable membranes as a dewatering method for a transfer station operated by Sanergy in Nairobi, Kenya. The objective was to determine if membranes could provide a sustainable and economically-feasible dewatering method within the constraints of Nairobi's informal settlements by evaluating multiple variables, such as flocculant dosage and initial total solids content, and their relation to faecal sludge dewatering. Experiments were conducted with several membrane types including commercial geotextiles and locally-produced plastic woven bags (gunny sacks). Increasing the flocculant dosage within an optimal range was seen to increase dewatering rates, but had minimal effect on the final dewatered solids content. Sludge with initial total solids contents below 3% was seen to require longer dewatering times to allow for drainage, while sludge above 3% required a minimal drainage period before evaporation began. A settling step proved paramount for sludge with high water content where the supernatant was then decanted prior to dewatering through permeable membranes; however, this may not be recommended in all cases depending on the treatment objectives. Reuse of geotextile membranes may lead to a reduction in dewatering performance, and single-use, locally-produced membranes are a more cost-effective, though operationally intensive, option. GRAPHICAL ABSTRACT: UF0001